Application of Jigsaw Strategy with Crossword Puzzle Media in Reading Skill Learning - Hasibuan, Renni; Fitriani, Laily; Aziz, Abdul (Al-Uslub: Journal of Arabic Linguistic and Literature, 2023)
This article aims to describe the application of the jigsaw learning strategy and crossword puzzle in maharah qiraah learning, which includes three aspects: 1) planning, 2) implementation, and 3) evaluation. This research uses a qualitative approach with descriptive method. The data used is in the form of information sourced from students majoring in Arabic Language and Literature at the State Islamic University of Maulana Malik Ibrahim Malang. Data collection technique used observation, interviews and documentation. In analyzing the data using the Miles and Huberman models, namely: data collection, data reduction, data presentation, and drawing conclusions. The research results are: 1) planning maharah qiraah learning by applying the jigsaw strategy and crossword puzzle media in the form of preparing a lesson plan and preparing crossword puzzle questions related to social text material. 2) implementation of maharah qiraah learning by applying the jigsaw model and crossword puzzle media in the form of opening activities namely class conditioning and delivery of learning objectives, and the core activity is studying qiraah material with the jigsaw model with the steps: instructing the jigsaw model, forming the original group, continuing to form expert group, after which each expert group presented the results of the discussion related to the paragraphs that had been discussed, evaluation from the lecturer. 3) evaluation is carried out by distributing crossword puzzle worksheets to each student and then they are welcome to work on each one.